Interpretable machine learning to identify important predictors of birth weight: A prospective cohort study - Liu, Zheng; Han, Na; Su, Tao; Ji, Yuelong; Bao, Heling; Zhou, Shuang; Luo, Shusheng; Wang, Hui; Liu, Jue; Wang, Hai-Jun (Frontiers in Pediatrics, 2022)
Background: Predicting birth weight and identifying its risk factors are clinically important. This study aims to use interpretable machine learning to predict birth weight and identity important predictors. Methods: This prospective cohort study was conducted in Tongzhou Maternal and Child Health Care Hospital of Beijing, China, recruiting pregnant women between June 2018 and February 2019. We used 24 features to predict infant birth weight, including gestational age, mother’s age, parity, history of macrosomia delivery, pre-pregnancy body mass index (BMI), height, father’s BMI, lifestyle (diet, physical activity, smoking), and biomarker (fasting glucose and lipids) features. Study outcome was birth weight of infant. We used 8 supervised learning models including 4 individual (linear regression, ridge regression, lasso regression, support vector machines regression (SVR)), and 4 ensemble estimators (random forest, AdaBoost, gradient boosted trees, and voting ensemble for regression) to predict birth weight. Model accuracy was measured by root mean squared error (RMSE) of 10-fold cross validation on the training set and RMSE of prediction on the test set. We used permutation importance algorithm to understand the prediction from the models and what affected them. Result: This study included 4754 mother-child dyads. RMSEs were lower in voting ensemble for regression, linear regression, and SVR than random forest, AdaBoost, and gradient boosted tree. The 5 most important predictors for infant birth weight were gestational age, fetal sex, preterm birth, mother’s height, and pre-pregnancy BMI. After adding ultrasound-measured indicators of fetal growth into predictors, mother’s height, and pre-pregnancy BMI remained the most important predictors in predicting the outcome. Conclusion: Mother’s height, and pre-pregnancy BMI were identified as important predictors for infant birth weight. Interpretable machine learning is a promising tool in the prediction of birth weight.